Key roles of autophagy in regulating T‐cell function. Issue 6 (9th June 2016) - Botbol, Yair; Guerrero‐Ros, Ignacio; Macian, Fernando
Abstract : Two distinct forms of autophagy, macroautophagy and chaperone‐mediated autophagy, are induced in activated T cells, where they participate in the regulation of a variety of processes, which range from the control of cell proliferation and survival to the regulation of T‐cell metabolism or the modulation of specific signaling pathways. Abstract : In the past 10 years, autophagy has emerged as a crucial regulator of T‐cell homeostasis, activation, and differentiation. Through the ability to adjust the cell's proteome in response to different stimuli, different forms of autophagy have been shown to control T‐cell homeostasis and survival. Autophagic processes can also determine the magnitude of the T‐cell response to TCR engagement, by regulating the cellular levels of specific signaling intermediates and modulating the metabolic output in activated T cells. In this review we will examine the mechanisms that control autophagy activity in T cells, such as ROS signaling and signaling through common gamma‐chain cytokine receptors, and the different aspect of T‐cell biology, including T‐cell survival, effector cell function, and generation of memory, which can be regulated by autophagy.